Karakter Visual pada Motif Ornamen Tegel Kunci Yogyakarta - Martino Dwi Nugroho (Institut Seni Indonesia Surakarta, 2010)
Tegel is the floor covering material having the appropriate char acteristics dengai cool tropical climate, strong, and durable. One of the tiles companies that still survive in Yogyakarta and has a long history is a Tegel Kunci company whose products have unique character. Based on the analysis can be seen that most of the motifs are using a variety of ornamental from Europe, especially the Gothic-style ornament. In addition to European decorative ornaments also widely used Islam or the style of